The Twits - "Dahl, Roald" (Scholastic: London, 2020)
Write interviews, play scripts, diary entries and instructions with the World's NUMBER ONE Storyteller! Get stuck in with The Twits and find your own remarkable reason to write. These super fun activities will help you to: * Improve language and vocabulary skills * Develop the tools you need to write your own stories * Learn how to use persuasive language, entertain your reader and add sparkle to non-fiction. Roald Dahl's Creative Writing will spark your creativity, build your confidence and inspire you through the wonderful worlds of Roald Dahl's best loved stories! Filled with top tips and ideas boxes, each book introduces techniques and methods to help you plan and write a phizz-whizzing story of your own!
Keywords: Fiction